Psychological factors that influence decision making about prophylactic surgery - Fang, Carolyn Y.; Mckenzie, Tamara; Miller, Suzanne M.; Daly, Mary B. (Psicooncología, 2005)
We reviewed the empirical literature on psychosocial factors influencing women’s decisions to undergo prophylactic surgery. A total of 34 studies were identified. The majority of studies found that women’s cancer-specific worries and risk perceptions exerted considerable influence in decision making about prophylactic surgery. Higher levels of cancerspecific anxiety were positively associated with interest in and intention to undergo surgery. In addition, greater perceived risk was also associated with greater interest and uptake of prophylactic surgery. Women also cited issues concerning body image and sexuality, familial responsibilities, and cultural norms as influencing the decision-making process. Several studies have begun to evaluate the impact of decision aids and counseling interventions, but additional studies are still needed to evaluate the long-term psychosocial, behavioral, and medical implications of these interventions. Decision counseling and preference clarification may be useful in facilitating the selection between different behavioral alternatives and in enhancing patient outcomes.